Neurological Findings in Anderson-Fabry Disease - Nicoletti, Angela; Sestito, Simona; Falvo, Francesca; Mascaro, Italia; Moricca, Maria Teresa; Salpietro, Vincenzo; Polizzi, Agata; Ruggieri, Martino; Bruno, Mercuri Francesco; Concolino, Daniela (Journal of Pediatric Biochemistry, 2016)
Anderson-Fabry disease (AFD) is an X-linked lysosomal storage disorder caused by mutations in the α-galactosidase A gene on chromosome Xq22, resulting in α-galactosidase A enzyme deficiency. It is characterized by progressive accumulation of lipids (e.g., globotriaosylceramide) in the lysosomes of a variety of cell types, including neural cells. Neurological manifestations, other than cerebrovascular accidents, include small fiber neuropathy and dysautonomic disorders. Small fiber peripheral neuropathy often is clinically manifested at young ages. Peripheral pain can be chronic and/or can occur as provoked attacks of excruciating pain. Manifestations of dysfunction of small autonomic fibers may include impaired sweating, gastrointestinal dysmotility, and abnormal pain perception. Patients with AFD often remain undiagnosed until the emergence of a more typical clinical manifestation, characterized by chronic renal and cardiac failure. Early clinical benefits of enzyme replacement therapy include reduction of neuropathic pain, and adequate management of residual pain to a tolerable and functional level, which can substantially improve the quality of these patients. Thus, it is important that physicians consider AFD in the differential diagnosis of neurological manifestations to provide an appropriate diagnostic and therapeutic workup.
Keywords: Fabry disease; neurological; α-galactosidase A; enzyme replacement therapy